2009
DOI: 10.1088/0953-4075/42/13/134018
|View full text |Cite
|
Sign up to set email alerts
|

Shell explosion and core expansion of xenon clusters irradiated with intense femtosecond soft x-ray pulses

Abstract: The disintegration mechanisms for xenon clusters in intense femtosecond soft x-ray pulses from the FLASH free electron laser are investigated. The clusters are irradiated at a wavelength of λ = 13.7 nm (hν = 90.5 eV) and power densities of 5 × 1014 W cm−2. During the 10 fs pulse the Xe clusters are transformed into a highly excited, multiply charged nanoplasma. Simulating the ion kinetic energies in an electrostatic model suggests that highly charged ions explode off the surface due to Coulomb repulsion while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 31 publications
10
97
0
Order By: Relevance
“…Their physical properties put them on the border between solid state and gas phase. Clusters are excellent objects to test the dynamics of samples irradiated with shortwavelength radiation from free-electron lasers (FELs) [1][2][3][4][5][6][7][8][9][10] and from high-harmonic-generation sources [11]. By studying the dependence of the cluster response on the cluster size, the influence of the atomic and condensed-matter effects on the ionization dynamics can be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their physical properties put them on the border between solid state and gas phase. Clusters are excellent objects to test the dynamics of samples irradiated with shortwavelength radiation from free-electron lasers (FELs) [1][2][3][4][5][6][7][8][9][10] and from high-harmonic-generation sources [11]. By studying the dependence of the cluster response on the cluster size, the influence of the atomic and condensed-matter effects on the ionization dynamics can be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we consider heterogeneous clusters composed of the noble gas atoms Xe and Ar, which have been extensively studied experimentally [1][2][3][4][6][7][8][9][10]. Using a fully nonequilibrium kinetic equation code (i.e., the Boltzmann solver described in [26,30,31]), we will demonstrate the significant effect of cluster composition on the ionization dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In dense nanoplasma, the cluster ionization can be further enhanced by energy-exchanging electron collisions [15]. For photon energies of % 100 eV, large clusters are transiently highly charged [16] before they disintegrate in a hydrodynamic expansion accompanied by recombination of the cluster core [17][18][19].…”
mentioning
confidence: 99%
“…It should be noted that our model assumes homogeneous plasma densities thus neglecting any shell effects [17] and starts at quasiequilibrium conditions. Charge redistribution within the nanoplasma and shell explosion can lead to a significant broadening of the ion distribution and higher observed charge states [18]. Further, FLYCHK does not take into account three-body recombination into higher Rydberg states above n ¼ 10, which have been shown to become significant for clusters explosions induced with intense infrared pulses after several ps of expansion [28].…”
mentioning
confidence: 99%
“…While IBS is predicted theoretically to provide strong contributions down to 62 nm [16], an electron spectroscopy experiment for Ar clusters at 32 nm [17] and an ion spectroscopy study for Xe clusters at 61 nm [18] found no evidence for IBS. Recent experimental results also revealed clear significance for other processes occurring during cluster ionization, such as sequential photoabsorption [17], charge recombination [19,20], and inhomogeneous charge redistribution [20,21]. A deeper insight into the spatial origin of the charge states can be obtained from core-shell heterogeneous systems.…”
Section: Introductionmentioning
confidence: 98%